Atomically precise and monolayer protected iridium clusters in solution. Issue 32 (11th March 2016) - Bhat, Shridevi; Chakraborty, Indranath; Maark, Tuhina Adit; Mitra, Anuradha; De, Goutam; Pradeep, Thalappil
Abstract : The first atomically precise and monolayer protected iridium cluster in solution, Ir9 (PET)6 (PET – 2-phenyethanethiol) was synthesized via a solid state method. Abstract : The first atomically precise and monolayer protected iridium cluster in solution, Ir9 (PET)6 (PET – 2-phenyethanethiol) was synthesized via a solid state method. The absence of a plasmonic band at ∼350 nm, expected in the UV/Vis spectra for spherical Ir particles of 10 nm size indicated that the synthesized cluster is smaller than this dimension. Small angle X-ray scattering (SAXS) showed that the cluster has a particle size of ∼2 nm in solution which was confirmed by transmission electron microscopy (TEM). The blue emission of the cluster is much weaker than many noble metal clusters investigated so far. X-ray photoelectron spectroscopy (XPS) measurements showed that all Ir atoms of the cluster are close to the zero oxidation state. The characteristic S–H vibrational peak of PET at 2560 cm −1 was absent in the FT-IR spectrum of the cluster indicating RS–Ir bond formation. The molecular formula of the cluster, Ir9 (PET)6 was assigned based on the most significant peak at m / z 2553 in the matrix assisted laser desorption ionization mass spectrum (MALDI MS), measured at the threshold laser intensity. Density functional theory calculations on small Ir@SCH3 and Ir@PET clusters and comparison of the predictions with the IR and 1 H-NMR spectra of Ir9 (PET)6 suggested that the PET ligands have two distinct structural arrangements and are likely to be present as bridging thiolates –(Ir–SR–Ir)– and singly attached thiolates –(Ir–SR).